2019
DOI: 10.1097/cm9.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific differences in non-cardiac comorbidities among elderly patients hospitalized with heart failure: a special focus on young-old, old-old, and oldest-old

Abstract: Background Despite the growing epidemic of heart failure (HF), there is limited data available to systematically compare non-cardiac comorbidities in the young-old, old-old, and oldest-old patients hospitalized for HF. The precise differences will add valuable information for better management of HF in elderly patients. Methods A total of 1053 patients aged 65 years or older hospitalized with HF were included in this study. Patients were compared among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…7 Clinical trials and real-world registries agree that the clinically stable mildly symptomatic HFrEF patient is a young-old (65-74 years old), overweight, male person with HF mainly due to ischaemic heart disease. 21,22 Despite the more favourable co-morbidity profile, this patient carries a considerable burden of coexisting conditions, more commonly coronary artery disease, hypertension, diabetes, atrial fibrillation, and chronic kidney disease. 9,23,24 The main symptom is dyspnoea on exertion and fatigue and less frequently overt signs or symptoms of HF, such as orthopnoea, paroxysmal nocturnal dyspnoea, dyspnoea at rest, peripheral oedema, and jugular vein distention.…”
Section: Clinical Characteristics Of Clinically Stable Mildly Symptommentioning
confidence: 99%
See 1 more Smart Citation
“…7 Clinical trials and real-world registries agree that the clinically stable mildly symptomatic HFrEF patient is a young-old (65-74 years old), overweight, male person with HF mainly due to ischaemic heart disease. 21,22 Despite the more favourable co-morbidity profile, this patient carries a considerable burden of coexisting conditions, more commonly coronary artery disease, hypertension, diabetes, atrial fibrillation, and chronic kidney disease. 9,23,24 The main symptom is dyspnoea on exertion and fatigue and less frequently overt signs or symptoms of HF, such as orthopnoea, paroxysmal nocturnal dyspnoea, dyspnoea at rest, peripheral oedema, and jugular vein distention.…”
Section: Clinical Characteristics Of Clinically Stable Mildly Symptommentioning
confidence: 99%
“…Clinical trials and real‐world registries agree that the clinically stable mildly symptomatic HFrEF patient is a young‐old (65–74 years old), overweight, male person with HF mainly due to ischaemic heart disease 21,22 . Despite the more favourable co‐morbidity profile, this patient carries a considerable burden of coexisting conditions, more commonly coronary artery disease, hypertension, diabetes, atrial fibrillation, and chronic kidney disease 9,23,24 .…”
Section: Clinical Characteristics Of Clinically Stable Mildly Symptommentioning
confidence: 99%
“…In gerontology, during the past 2 decades, older adults have often been subdivided into three categories: young‐old (65–74 years old), old‐old (75–84 years old) and oldest‐old (≥85 years old; Crews & Zavotka, 2006). Previous studies have shown specific differences in general and clinical characteristics in age‐specific groups (Koo et al, 2017; Salive, 2013; Yang et al, 2019). In addition, not only did the factors affecting or related to each health outcome differ, the effect of intervention was also different in age‐specific groups (Cho et al, 2017; Noh et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…Elderly patients with HF represent a vulnerable group with a wide range of somatic and mental comorbidities ( 3 , 4 ) leading to low health related quality of life ( 5 ). This complicated clinical picture may result in complex drug-to-drug interactions due to polypharmacy ( 6 8 ), poor medical adherence ( 6 ) and increased hospitalizations and mortality rates ( 8 , 9 ). All of these factors contribute to a higher dependency in self-care and daily activities ( 10 ).…”
Section: Introductionmentioning
confidence: 99%